Hepatic Artery Delineation on Ultrasound Volumes Comparing B-Flow and Color Doppler for Postoperative Monitoring of Pediatric Liver Transplants - Elena Dammann; Leonhard Steinmeister; Michael Groth; Uta Herden; Lutz Fischer; Florian Brinkert; Jan Beime; Magdalini Tozakidou; Peter Bannas; Jochen Herrmann (Diagnostics, 2024)
(1) Background: Accurate hepatic artery (HA) depiction following pediatric liver transplantation (LT) is essential for graft surveillance but challenging on ultrasound (US). This study assesses if improved HA delineation can be achieved by recording two-dimensional US volumes in Color Doppler (CD) and B-flow technique. (2) Methods: Of 42 consecutive LT, 37 cases were included, and HA delineation was retrospectively rated using a four-point score (0 = HA not detectable, 3 = HA fully detectable, separable from portal vein) within 48 h post-LT (U1) and before discharge (U2). (3) Results: Adding B-flow compared with CD alone showed superior results at neohilar (U1: 2.2 ± 1.0 vs. 1.1 ± 0.8, p < 0.0001; U2: 2.5 ± 0.8 vs. 1.5 ± 0.9, p < 0.0001) and segmental levels (U1: 2.8 ± 0.6 vs. 0.6 ± 0.8, p < 0.0001; U2: 2.8 ± 0.6 vs. 0.7 ± 0.5, p < 0.0001). (4) Conclusions: Standardized US volume recordings combining B-flow and CD can effectively delineate the HA along its vascular course in pediatric LT. The technique should be further evaluated as a standard monitoring instrument to rule out vascular complications after LT.